Effect of rainfall on the yield of major cereals in Darchula District of Nepal - Bhandari, Govinda (International Journal of Environment, 2014)
Rainfall is one of the most important factors for the growth of cereals. Inadequate water results poor growth and reduced yield. This study is aimed to explore the relationship between rainfall and yield of major cereals in Darchula district of Nepal. The yield of individual cereals is correlated with the seasonal rainfall data using MS Excel to identify the effect of rainfall on yield of cereals. The amount of rainfall in the years 1974, 1977, 1980, 1985, 1986, 1987, 1991, 1992, 1994, 1996, 1997, 1999 and 2000 was reduced which has greatly affected the yield of rice, wheat and maize in 1986 and 1987. In the years 1976, 1977, 1999 and 2000, the decrease in the amount of rainfall has reduced the yield of all major cereals in Darchula district of Nepal. DOI: http://dx.doi.org/10.3126/ije.v3i1.9954 International Journal of Environment Vol.3(1) 2014: 205-213